Über den Rang der Polyeder der besten Approximationen im Raume der stetigen Funktionen - Romanova, Z. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: З. С. Романова. О размерности многогранников наилучших приближений в пространстве непрерывных функций Z. Romanova. Geriausiųjų tolydinės funkcijos aproksimacijų poliedro rangas